2020
DOI: 10.1101/2020.07.16.20155523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of climate temperature on counts, recovery, and death rates due to SARS-CoV-2 in South Africa

Abstract: The impact of climate temperature on the counts (number of positive COVID-19 cases reported), recovery, and death rates of COVID-19 cases in all of South Africa's 9 provinces was investigated. The data for confirmed cases of COVID-19 were collected for March 25 and June 30, 2020 (14 weeks) from South Africa's Government COVID-19 online resource, while the daily provincial climate temperatures were collected from the website of the South African Weather Service. Our result indicates that a higher or lower clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Notably, although SARS-CoV-2 first spread in the temperate zone ( Chennakesavulu and Reddy, 2020 ; Huang et al, 2020 ; Sajadi et al, 2020 ; Sarmadi et al, 2020 ), India and Singapore are located outside the temperate zone, while Norway is at the most northern edge of the temperate zone. Interestingly, some studies also reported no correlation between temperature and the local transmission of SARS-CoV-2 ( Briz-Redón and Serrano-Aroca, 2020 ; Chetty et al, 2020 ; Harbert et al, 2020 ; Wu et al, 2020a ; Yao et al, 2020b ) ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, although SARS-CoV-2 first spread in the temperate zone ( Chennakesavulu and Reddy, 2020 ; Huang et al, 2020 ; Sajadi et al, 2020 ; Sarmadi et al, 2020 ), India and Singapore are located outside the temperate zone, while Norway is at the most northern edge of the temperate zone. Interestingly, some studies also reported no correlation between temperature and the local transmission of SARS-CoV-2 ( Briz-Redón and Serrano-Aroca, 2020 ; Chetty et al, 2020 ; Harbert et al, 2020 ; Wu et al, 2020a ; Yao et al, 2020b ) ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study also showed that average temperature and sunshine duration were not significantly associated with the transmission of COVID-19 outbreaks, for the entire cumulative lag days during the study period in Addis Ababa. Studies in South Africa, Canada, Australia, and Pakistan also reported a non-significant association between temperature and COVID-19 incidence 14,[24][25][26] . In contrast to these findings, studies conducted in India and Bangladesh found that increasing temperature was significantly associated with increasing number of COVID-19 cases 12,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Most research on environmental and meteorological effects with COVID-19 fatality has provided simple correlation coefficients or mapped global COVID-19 deaths against the global pattern of temperature changes resulting in predictions that these deaths would increase as the weather became warmer in spring 32–40 . Two time-series studies explored the relationship between temperature changes and COVID-19 deaths for specific cities in China and found that higher temperatures were associated with more deaths 41,42 .…”
mentioning
confidence: 99%